Twenty years of central banking in Nigeria : 1959-1979 - Central Bank of Nigeria (Lagos : Research Dept., Central Bank of Nigeria, 1979)
The book, intended to document the twenty year experience of the Central Bank of Nigeria, is written to commemorate its twentieth anniversary. It unravels the intricacies of the functioning of a central bank in a less financially sophisticated economy.
osc 3/5/18
Loans
Keywords: Banks and banking